Influence of motivative factors on the performance of civil servants - O.V. Lytvynchuk (Економіка, управління та адміністрування)
The article is devoted to the issue of motivation of civil servants. We conducted a thorough analysis of publications on the problem of motivation. The analysis of publications showed the presence of a significant amount of research on this issue. The topical problems of motivation of civil servants in modern conditions are substantially considered. The main motives of employees are determined and the essence of work motivation is analyzed, the main tasks of motivation are listed. Depending on the results of human activity, motivation may change. This causes a change in behavior in the process of doing work. To successfully manage the behavior of a civil servant in the work process, it is important to establish why a person works, what causes the desire and need to work. Only under the influence of strong motivational factors diligence and persistence in achievement of the purposes is formed. Motivation enhances the desired human behavior. Understanding the internal mechanisms of motivation is an important component of an effective policy of professional relations in the field of public administration. We have considered the main areas of material and intangible motivation of civil servants as a factor in improving efficiency. Theoretical problems of motivation system formation are reflected. If employees are not properly motivated to work highly efficiently, it reduces the overall level of activity of the enterprise and its competitiveness. Modern methods of motivating civil servants and their impact on performance are considered. A civil servant should be satisfied with his / her work, receive appropriate results and rewards, get acquainted with his / her successes, receive recognition for his / her work and see further prospects in his / her own activity. In the process of scientific research such methods as descriptive and analytical, induction and deduction, analysis, synthesis were used for processing materials, which provided an opportunity to fully and systematically investigate this issue.